Ansiedad y actitudes ante la muerte: revisión y caracterización en un grupo heterogéneo de profesionales que se capacita en cuidados paleativos - Grau Abalo, Jorge (2022)
Nowadays society reinforces an evasive attitude towards death. Health professionals, for different reasons, show anxiety and attitudes that do not always help sick people (and their relatives) when life is coming to an end. A review of the topic is presented, highlighting the need to develop a style of intervention which will change negative attitudes towards death on the part of these professionals, resulting in an improvement of the quality of attention they give. Previous work has achieved a preliminary characterization in small and homogeneous groups, according to professional profile. This study describes the attitude-related components regarding death in 141 Cuban professionals, from different profiles who are being trained in palliative care, through their answers to a questionnaire (Attitudes Towards Death Questionnaire-ATDQ-2), previously validated in the country. At the time of the study, these professionals receive Palliative Care Courses, but not a specially-designed intervention to alter affective attitude-related components. The results of this study are presented and compared with previous research.